The Effects of Leg Preference on Transient Characteristics of Body Sway During Single-Leg Stance: A Cross-Sectional Study - Kozinc, Žiga; Šarabon, Nejc (Frontiers in Human Neuroscience, 2021)
Instrumented assessments of quiet-stance postural control typically involve recording and analyzing of body sway signal, most often the center of pressure (CoP) movement. It has been recently suggested that transient characteristics of body sway may offer additional information regarding postural control. In this study we explored the relationship between whole-trial estimates of body sway (CoP velocity, amplitude, and frequency) and corresponding transient behavior indexes, as well as the effects of leg preference. A total of 705 healthy young athletes performed 30-s single-leg body sway trials for both legs. It was found that the transient characteristics of the body sway (expressed as relative differences between individual time intervals within the trial) are in negligible or weak correlation (r ≤ 0.26) with the corresponding variables, averaged across the whole trial. All CoP variables showed transient characteristics, reflected in statistically significant decrease (CoP velocity and amplitude) or increase (CoP frequency) throughout the trial. The preferred leg showed smaller body sway, however, the effects sizes were very small. Moreover, differences between the legs were also noted in terms of transient characteristics of body sway. In particular, the preferred leg showed earlier reduction in anterior-posterior body sway and larger reduction in medial-lateral body sway. Further studies should focus on examining the clinical utility of indexes of transient behavior of body sway, for instance, their sensitivity to ageing-related changes and risk of falling.